Functional Characterization of a LOV‐Histidine Kinase Photoreceptor from Xanthomonas citri subsp. citri1. (20th August 2015) - Kraiselburd, Ivana; Gutt, Alexander; Losi, Aba; Gärtner, Wolfgang; Orellano, Elena G.
Abstract The blue‐light (BL) absorbing protein Xcc‐LOV from Xanthomonas citri subsp. citri is composed of a LOV‐domain, a histidine kinase (HK) and a response regulator. Spectroscopic characterization of Xcc‐LOV identified intermediates and kinetics of the protein's photocycle. Measurements of steady state and time‐resolved fluorescence allowed determination of quantum yields for triplet (ΦT = 0.68 ± 0.03) and photoproduct formation (Φ390 = 0.46 ± 0.05). The lifetime for triplet decay was determined as τT = 2.4–2.8 μs. Fluorescence of tryptophan and tyrosine residues was unchanged upon light‐to‐dark conversion, emphasizing the absence of significant conformational changes. Photochemistry was blocked upon cysteine C76 (C76S) mutation, causing a seven‐fold longer lifetime of the triplet state (τT = 16–18.5 μs). Optoacoustic spectroscopy yielded the energy content of the triplet state. Interestingly, Xcc‐LOV did not undergo the volume contraction reported for other LOV domains within the observation time window, although the back‐conversion into the dark state was accompanied by a volume expansion. A radioactivity‐based enzyme function assay revealed a larger HK activity in the lit than in the dark state. The C76S mutant showed a still lower enzyme function, indicating the dark state activity being corrupted by a remaining portion of the long‐lived lit state.